1994
DOI: 10.1213/00000539-199407000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High-Dose Thrombin Time with Activated Clotting Time for Monitoring of Anticoagulant Effects of Heparin in Cardiac Surgical Patients

Abstract: The activated clotting time (ACT) is routinely used for monitoring of heparin effects during cardiopulmonary bypass (CPB). However, ACT is not a specific assay for heparin and may be influenced by several other factors, which may be misleading with regard to the proper administration of heparin and protamine. In this pilot study, we compared a new test, the high-dose thrombin time (HiTT), with the conventional ACT test for both in vitro and in vivo heparin-induced anticoagulation. Our in vitro results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Andrew et al (10) showed that although there was a correlation between plasma heparin concentration and ACT values when blood of adult persons was previously drawn into syringes containing heparin, there was no correlation when the test was performed with blood of their pediatric patients. Wang et al (11) reported that although a linear response of ACT to heparin levels in the blood of their patients was observed in vitro, this correlation was lost during CPB due to hypothermia. Chan et al (12) observed that ACT values did not correlate to heparin concentration during cardiopulmonary bypass, likely due to activation of the clotting system and platelets, hypothermia, and hemodilution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Andrew et al (10) showed that although there was a correlation between plasma heparin concentration and ACT values when blood of adult persons was previously drawn into syringes containing heparin, there was no correlation when the test was performed with blood of their pediatric patients. Wang et al (11) reported that although a linear response of ACT to heparin levels in the blood of their patients was observed in vitro, this correlation was lost during CPB due to hypothermia. Chan et al (12) observed that ACT values did not correlate to heparin concentration during cardiopulmonary bypass, likely due to activation of the clotting system and platelets, hypothermia, and hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the heparin level is increased to 1.0 U/ml, ACT most likely will be significantly higher than in a lower heparin level. This indicates that heparin is reflected by ACT only poorly and could explain why a correlation between ACT and heparin levels was not found in vivo (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The High Dose Thrombin Time (HiTT, Hemochron) is more specific to heparin effects than the activated clotting time [ACT] (Wang et al, 1994) In contrast to the ACT, the HiTT is not altered by haemodilution or hypothermia. However, both before and during CPB there is poor correlation between the HiTT and ACT and for individual patients a target HiTT of 190 s may not equate to an adequate ACT of 480 s. In such cases, therefore, a comparative ACT/HiTT assay may be required to establish a therapeutic HiTT time (de Jong, 1999).…”
Section: Modifications Of the Thrombin Timementioning
confidence: 99%
“…Given the good correlation of the ACT to the anticoagulant effects of heparin, its role has principally been in monitoring this effect during both surgical and catheter-based procedures [9 -18]. The ACT, however, is not a specific assay for monitoring the effect of heparin and can be affected by factors other than heparin, such as hemodilution, hypothermia, disseminated intravascular coagulation, platelet dysfunction, or hypercoagulability [26,27]. As aspirin affects platelet function indirectly, it too, may alter the correlation between ACT value and coagulability.…”
Section: Discussionmentioning
confidence: 99%